Community Service of Competitiveness Improvement of Elo River Rafting Tourism Magelang Regency - Muhlisin, Ahmad; Siswanto, Siswanto; Al Firdaus, Moch Malik (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2021)
Local and foreign tourists visit potential in Elo River rafting tourism evinces an increase every year. Therefore, it is important to improve management and human resource skills. This community service (Pengabdian Kepada Masyarakat/PKM) aims to improve Elo River rafting tourism competitiveness through the development of integrated website, Statutes and Bylaws (AD/ART), Standard Operating Procedures (SOP), and enhancement of English communication skill. The service methods are applied using direct methods from preparation, implementation, and evaluation. The results of activities implementation indicate that the activities are well implemented in accordance with the pre-determined targets and outcomes. The activities executed provide an illustration that it produces added values; thus it improves the competitiveness of Elo River operator association. Follow-up efforts of the implemented programs include cooperation between Universitas Tidar and the Elo River rafting association in the efforts of competitiveness improvement in terms of English Skills and the administration of competence test for tour guides.